High resolution X-ray photoemission of SrCu2O2 - Lynch, C; Egdell, R; Law, D (2005)
Pure and K-doped SrCu 2O 2 have been studied by high resolution X-ray photoemission spectroscopy. Valence band photoemission spectra are shown to be in good agreement with the bandstructure calculations of Ohta et al. and are dominated by the Cu 3d partial density of states. Conductivity measurements reveal that the Fermi level in nominally undoped material is pinned by acceptor states 0.24 eV above the valence band edge but moves toward the valence band with increasing doping. Changes in core and valence level binding energies with doping mirror the changes in the transport activation energy. © 2004 Elsevier B.V. All rights reserved.